A detailed explantation assessment protocol for patients with left ventricular assist devices with myocardial recovery. (19th November 2020) - Monteagudo Vela, María; Rial Bastón, Verónica; Panoulas, Vasileios; Riesgo Gil, Fernando; Simon, Andre
Abstract: OBJECTIVES: Left ventricular assist device (LVAD) implantation for end-stage heart failure patients has been on the rise, providing a reliable long-term option. For some LVAD patients, longer term LV unloading leads to recovery; hence, the need for evaluating potential myocardial recovery and weaning eligibility has emerged. METHODS: All patients who underwent contemporary LVAD explantation at our institution between 2009 and 2020 were included in the study. Patients in New York Heart Association I, left ventricular ejection fraction >40%, a cardiac index >2.4 l/min and a peak oxygen intake >50% predicted underwent a 4-phase weaning assessment. A minimally invasive approach using a titanium plug was the surgery of choice in the most recent explants. Kaplan–Meier curves were used to estimate the survival at 1 and 5 years. RESULTS: Twenty-six patients (17 HeartMate II, 9 HeartWare) underwent LVAD explantation after a median 317 days of support [IQ (212–518)], range 131–1437. Mean age at explant was 35.8 ± 12.7 years and 85% were males. Idiopathic dilated cardiomyopathy was the underlying diagnosis in 70% of cases. Thirteen (48%) patients were on short-term mechanical circulatory support and 60% required intensive care unit admission prior to the LVAD implantation. At 1 year, Kaplan–Meier estimated survival was 88%, whereas at 6 years, it was 77%. The average left ventricular ejection fraction at 1 year post-explant was 44.25% ± 8.44. CONCLUSIONS: The use of a standardized weaning protocol (echocardiographic and invasive) and a minimally invasive LVAD explant technique minimizes periprocedural complications and leads to good long-term device-free survival rates. Abstract : Physicians are faced with a prevalence of >25 million heart failure (HF) cases worldwide [1].